Perbedaan Hasil Rias Mata Hooded antara yang Menggunakan Teknik Jahit Bulumata dan Eyelid Tape - Sabillah, Syifa Salsa; Irtawidjajanti, Sri; Atmanto, Dwi (Innovative: Journal Of Social Science Research, 2025)
Hooded eyes are an imperfect eye shape where the upper eyelid covers the eye crease, making the natural crease less visible when the eyes are open and causing eye makeup to be less visible. This study aims to determine the differences in hooded eye makeup results between those using eyelash sewing and eyelid tape techniques. This research method uses quantitative research with an experimental research type. The sample in this study were 10 hooded eyes in women aged 15-35 years who have yellow skin color. Data collection techniques used observation and documentation. Data analysis techniques used were normality test, homogeneity test, and t-test (independent sample test). The results of the normality test in the eyelash sewing group were 0.829 > 0.05 which means normal distribution, while the results of the normality test in the eyelid tape group were 0.931 > 0.05 which means normal distribution. The results of the homogeneity test have a significance value greater than the 0.05 level which is normally and homogeneously distributed. The results of the hypothesis test using the t-test (independent sample test) showed a P-value of 0.373 > 0.05, a calculated t-value of -0.944, and a t-table of 8, indicating that H0 is accepted and Ha is rejected. This indicates that there is no significant difference between the results of hooded eye makeup using the sewn-in eyelash technique and eyelid tape. Based on the judges' assessment indicators, the use of eyelid tape received the highest score of 13.666, while the sewn-in eyelash technique received 13.134. The results of this study can be used as a guide for makeup artists and individuals to determine the difference between hooded eye shapes using the sewn-in eyelash technique and eyelid tape.